Epidemiology of Male Sexual Dysfunction in Asian and European Regions: A Systematic Review. Issue 4 (July 2020) - Irfan, Muhammad; Hussain, Nik Hazlina Nik; Noor, Norhayati Mohd.; Mohamed, Mahaneem; Sidi, Hatta; Ismail, Shaiful Bahari
Male sexual dysfunctions (MSDs) often remain undiagnosed and untreated in Asia compared to Europe due to conservative cultural and religious beliefs, socioeconomic conditions, and lack of awareness. There is a tendency for the use of traditional medicines and noncompliance with and reduced access to modern healthcare. The present systematic review compared the incidence and factors of MSD in European and Asian populations. English language population/community-based original articles on MSDs published in MEDLINE from 2008 to 2018 were retrieved. A total of 5392 studies were retrieved, of which 50 (25 Asian and 25 European) were finally included in this review. The prevalence of erectile dysfunction (ED) (0%–95.0% vs. 0.9%–88.8%), low satisfaction (3.2%–37.6% vs. 4.1%–28.3%), and hypoactive sexual desire disorder (HSDD) (0.7%–81.4 vs. 0%–65.5%) was higher in Asian than in European men, whereas the prevalence of anorgasmia (0.4% vs. 3%–65%) was lower in Asian than in European men. Age was an independent positive factor of MSD. In European men over 60 years old, the prevalence of premature ejaculation (PE) decreased. The prevalence of MSD was higher in questionnaires than in interviews. The significant factors were age, single status, low socioeconomic status, poor general health, less physical activity, cardiovascular diseases, diabetes, obesity, lower urinary tract symptoms, prostatitis, anxiety, depression and alcohol, tobacco, and drug use. The prevalence of MSD differed slightly in Asian and European men. There is a need to conduct large studies on the various Asian populations for the effective management of MSD.